CRIMINAL LAW POLICY FOR FOREST PROTECTION IN INDONESIA (A STUDY ON FOREST DESTRUCTION CRIME IN MEDAN, NORTH SUMATERA) - Anita Zulfiani; Nabila Alinka Wibowo; Muna Ganesya Arya (Universitas Sebelas Maret (UNS), 2026)
Indonesia's role is very important in preventing global temperature rise because Indonesia is considered the